Welcome to Westonci.ca, the place where your questions find answers from a community of knowledgeable experts. Find reliable answers to your questions from a wide community of knowledgeable experts on our user-friendly Q&A platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.

Determine if the equation has no solution,one solution, or infinite many solution.

Give an explanation step by step.

-2(11-12)=-4(1-6x)​


Sagot :

Answer:

Step-by-step explanation:

-2(11-12)=-4(1-6x)​ becomes -2(-1) = -4(1 - 6x)

Next, we divide both sides by -2, obtaining -1 = 2(1 - 6x), and then

                                                                        -1 = 2 -12x, or

                                                                         -3 = -12x

Simplifying this result, we get 1 = 4x, or x = 1/4

We conclude that -2(11-12)=-4(1-6x)​ has ONE solution, which is x = 1/4

Thank you for choosing our service. We're dedicated to providing the best answers for all your questions. Visit us again. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.